Hydrocortisone as an adjunct to brief cognitive-behavioural therapy for specific fear: endocrine and cognitive biomarkers as predictors of symptom improvement - Steudte-Schmiedgen, S; Fay, E; Capitao, L; Kirschbaum, C; Reinecke, A (SAGE Publications, 2021)
Background: Glucocorticoid (GC) administration prior to exposure-based cognitive-behavioural therapy (CBT) has emerged as a promising approach to facilitate treatment outcome in anxiety disorders. Further components relevant for improved CBT efficacy include raised endogenous GCs and reductions in information-processing biases to threat.